Struktur Vegetasi Riparia dan Implikasinya Terhadap Kondisi Habitat Ikan Pelangi Arfak, Melanotaenia Arfakensis di Sungai Nimbai, Manokwari Papua Barat - Paskalina Th. Lefaan; Hans Fence Zakeus Peday; Simon Petrus Oktovianus Leatemia; Luky Sembel; Emmanuel Manangkalangi (Faculty of Science and Technology University Ibrahimy, 2019)
Riparian vegetation has an important role in maintaining water stability, one of which is the river. This study aims to describe the structure of riparian vegetation so that its implications can be seen for the conditions of rainbow arfak habitat on the Nimbai River. The study was conducted in three forest types, namely primary riparia forest, secondary riparia forest and open riparia forest. Sample collection of riparian vegetation was carried out by purposive sampling using sample plots. Plots measuring 2 m x 2 m are used to sample seedling and understorey growth, plots measuring 5 m x 5 m for growth at the stake level, while plots measuring 10 m x 10 m and 20 m x 20 m, for growth of pole and tree levels respectively. The identification results obtained a total of 35 species of understorey and 51 tree-level plants in all three types of riparian forests. Based on the analysis of vegetation structure, it is known that the condition of primary riparia forest and secondary riparian forest still relatively supports the life of arfak rainbow fish compared to open riparian forest. Higher tree level density associated with canopy cover which has implications for the temperature of the water to be colder and less fluctuating, input larger litter into the food chain in the river, and hold suspended particles into the river. Also, the function of riparian vegetation in spawning activities, substrate attaching eggs and nursery habitat for arfak rainbow fish larvae. The results of this study indicate the importance of riparian vegetation structure on the condition of rainbow arfak fish habitat. An understanding of the structure of vegetation is also a basic information for efforts to rehabilitate this endemic fish habitat to maintain the existence of a natural population.